Seismic fragility assessment of low-rise reinforced concrete frame: A comparative study of bare and infill model - Suwal, Rajan; Uprety, Rupesh (Journal of Engineering Issues and Solutions, 2023)
Most of the residential structures designed in Nepal are low-rise reinforced concrete (RC) frames. They are designed following the guidelines given in the Nepal Building Code, especially, the mandatory rule of thumb. In analyzing and designing most of the reinforced concrete structures in the urban and semi urban areas of Nepal, only bare frame model is considered. The additional effect caused by the infill walls are neglected. In this research, a comparative seismic fragility assessment of low-rise RC frame is conducted. Two cases are assumed; with and without the consideration of the unreinforced masonry infill. Macro modelling approach is followed for modelling the infill effect. Results clearly indicate that the inclusion of the infills drastically reduce the roof displacement compared to the bare frame model during a seismic shaking. This is attributed to the fact that the inclusion of the infill imparts more stiffness to the structure during a seismic-shaking compared to the bare frame model and hence the displacement is reduced. Furthermore, seismic fragility of the frame structure is also overstated when the effect of infill is not taken into consideration. The inclusion of infills reduced the structural fragility to significant extent. In this regard, the bare frame model was found to be more vulnerable to seismic shaking compared to the infill model.